Dormência em espécies arbóreas de dois biomas brasileiros - Rodrigues Filho, Josinei (2017)
Dormancy can be defined as a blockage of the viable seed germination process, even when exposed to favorable environmental conditions. This impediment is found in a large number of forest species of the most varied biomes. In the Brazilian territory six different biomes are found, among them two presenting marked differences in water availability. They are: the Dense Ombrophylous Forest, represented by the Amazonian and Atlantic Forest, and the Cerrado. Studies showing a clear relation between dormancy and the biome in which the species occurs are still scarce. The objective of this work was to verify in the chapter one, through a bibliographical survey, a possible association between the occurrence of seed dormancy of native forest species and different biomes (Dense Ombrophylous Forest and Brazilian Cerrado), among ecological groups (pioneers and climaxes) and in relation to the botanical families, as well as to test, in chapter two, the efficiency of several treatments to overcome the dormancy of Senna pendula, a Brazilian forest species, and perform the morphological characterization of its seeds. A hundred species of each biome were randomly sampled and in order to verify the possible association between the factors and the Pearson's Qui-square test was performed. Seeds of Senna pendula (native to the Dense Ombrophylous Forest) were submitted to several treatments for breakage of dormancy: a) mechanical scarification of the integument opposite the embryo with sandpaper nº 40 for 30 seconds; B) immersion in hot water at 70 ºC for 5, 10, 15 and 20 minutes; C) immersion in hot water at 90 ° C for 5, 10, 15 and 20 minutes; D) immersion in concentrated sulfuric acid (H2SO4) for 5, 10, 15 and 20 minutes, followed by washing under running water; and e) seeds without treatment (control). The bibliographic survey showed that although the Cerrado had a slightly higher dormancy percentage when compared to the forest (54 to 47%), this difference was not significant. The independence of factors was also observed in the correlation with the ecological groups, which means that there was no association between the variables analyzed. The seeds of Senna pendula present physical dormancy characterized by a thick tegument layer which prevents the absorption of water from the medium. The most effective treatments to overcome dormancy were mechanical and chemical scarification with a percentual of germination up to 94%